2014
DOI: 10.1002/app.41370
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity evaluation of hydrogel–carbon nanotubes composites on intestinal cells

Abstract: Composite materials based on carbon nanotubes (CNT) and polymeric hydrogels have become the subject matter of major interest for use as carriers in drug delivery research. The aim of this study was to evaluate the in vitro cytotoxicity of the hydrogel–carbon nanotube–chitosan (hydrogel–CNT–CH) composites on intestinal cells. Oxidized CNT were wrapped with chitosan (CH), Fourier transform infrared (FT‐IR) analysis suggest that oxidized CNT interact with CH. Transmission electron microscopy (TEM) images show a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In order to obtain antibacterial polymeric nanocomposites, CH wrapped CNT were incorporated into pH-sensitive hydrogels. In our previous study, we have shown that the addition of CH wrapped CNT to the hydrogels improved the properties of these nanocomposites without affecting their biocompatibility [9] offering new opportunities for the treatment of certain infectious diseases [3,15]. In this work, we prepared hydrogel-(CNT-CH) nanocomposites that were characterized and checked for antimicrobial activity against S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain antibacterial polymeric nanocomposites, CH wrapped CNT were incorporated into pH-sensitive hydrogels. In our previous study, we have shown that the addition of CH wrapped CNT to the hydrogels improved the properties of these nanocomposites without affecting their biocompatibility [9] offering new opportunities for the treatment of certain infectious diseases [3,15]. In this work, we prepared hydrogel-(CNT-CH) nanocomposites that were characterized and checked for antimicrobial activity against S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…The composites were synthesized according to previously reported methodologies [9]. AAm (Aldrich) and AAc (Aldrich) were used as monomers.…”
Section: Synthesis Of Hydrogel-cnt-ch Compositesmentioning
confidence: 99%
“…Several methods have been developed to protect IgY from degradation by pH and pepsin present in the stomach, allowing it to arrive unscathed at the small intestine, which is especially important for the use of IgY against enteric pathogens. Among these treatments, chitosan and alginate microcapsules [29], β-cyclodextrin microcapsules [30,31], copolymers of methacrylic acid [32], liposomes [31,33], multiple emulsification [34], hydrogel [35] and carbon nanotubes with hydrogel [36] have been tested with different degrees of success. Nonetheless, unprotected IgY consumed as egg yolk in liquid [37] and powder forms [38] showed resistance to the gastrointestinal tract conditions in calves.…”
Section: Structural and Biochemical Properties Of Igymentioning
confidence: 99%
“…In terms of mechanical, optical, conductive, and thermal properties, carbon nanotubes (CNTs) have received enormous attention in the field of bioapplications. [151][152][153] Although many research groups have incorporated CNTs into hydrogel polymers 154 in order to reinforce gel structure, increase electrical conductivity, and enhance NIR sensitivity properties, only a few studies have reported the preparation of the CNT-nanogel composite for drug delivery purposes. 23,24,155 Nevertheless, this is a topic that will be much studied in the forthcoming years.…”
Section: Other Nanomaterials-nanogels: Quantum Dots Porous Silica Namentioning
confidence: 99%